Understanding and Perception of Women Career Towards The Principles of Ubudiyyah, Mas'uliyyah and Itqan - Noor Fatimah Mujahid; Nur Aina Mardhiah Che Rahim; Amrina Rasyada Kamaruzaman (Rabbanica: Journal of Revealed Knowledge)
The value of Rabbani manners in work and the code of ethics used by public nurses in Kelantan is based on the principles of Ubudiyyah, Mas’uliyyah, and Itqan. Thus, the purpose of the study is to evaluate how well-working women in Kelantan comprehend and apply the UMI (Ubudiyyah, Mas'uliyyah, and Itqan) principles in their daily lives. This study combined a qualitative literature review and a quantitative approach using a probe form. The results show that most working women in Kelantan know and understand the UMI principles as a guide in their work. In addition, the UMI principles help them carry out their tasks at work with more discipline, dedication, caliber, and diligence. In addition, this principle tells working women that working is an act of worship to Allah SWT and allows them to devote their time to their household affairs. Finally, the UMI principle is a clear reference and guide for most working women. This shows that the effort to popularize Building Together Islam has reached a high level of success, especially among women. However, to make the implementation of UMI principles more comprehensive and more user-friendly, there is still room for improvement. It is hoped that the study and recommendations will help the committee that has been appointed by the state government to improve the system and approach in applying understanding related to UMI in career. Indirectly helping Kelantan female civil servants get a comprehensive moral support system to carry out their dutie.